Expression of inflammatory cytokines in mesenchymal stem cells derived from proximal humerus fractures - Viveiros, Magda Massae Hata [UNESP]; de Melo Viveiros, Márcio Eduardo [UNESP]; Silva, Márcia Guimarães [UNESP]; Kaneno, Ramon [UNESP]; Avelino, Natália Porfírio [UNESP]; Rainho, Cláudia Aparecida [UNESP]; Schellini, Silvana Artioli [UNESP] (AME Publishing Company, 2022)
Background: Mesenchymal stem cells (MSCs) are an excellent treatment option for a wide variety of orthopaedic conditions. This study aimed to establish if bone marrow MSCs obtained from proximal humerus fractures can be an alternative source for obtaining primary cultures of human MSCs. Methods: Human bone marrow was obtained during osteosynthesis surgeries on closed proximal humerus fractures within 48 hours of injury. MSCs were harvested using the Ficoll gradient separation protocol and in vitro cultured until the third passage. Then, the cells were immunophenotyped by flow cytometry using stem cell specific surface markers. The cells were also induced to differentiate into osteoblasts and adipocytes for the characterization and confirmation of MSCs. The production of cytokines interleukin (IL)-1β, IL-6, IL-8, IL-10, tumor necrosis factor α (TNF-α), and interferon γ (IFN-γ) was assessed using enzyme-linked immunosorbent assay (ELISA) in the supernatant of the cultures after 3, 5 or 7 days. Results: Immunophenotyping showed high expression of the stem cell surface markers CD73, CD90, and CD105 and negative or very low expression of CD34, CD45, CD11b, CD19, and human leukocyte antigen (HLA)-DR. The bone marrow derived MSCs were able to differentiate into osteoblasts and adipocytes. The quantification of secreted cytokines revealed that IL-8 was the most produced cytokine, followed by IL-6 and IL-10 at similar quantities and lower levels of IL-1β. TNF-α and IFN-γ were not detected. Conclusions: Proximal humerus fractures can be an alternative source for the collection of bone marrow MSCs. The cytokine production of these cells is very similar to the production profile of fracture haematomas previously reported and may be used for improving bone repair.
Keywords: bone repair; cytokines; fracture situs; Human bone marrow mesenchymal stem cells; in vitro culture